A Bibliometric Review of Arab World Research from 1980-2020. Issue 2 (3rd April 2021) - Ahmad, Shakil; Ur Rehman, Shafiq; Ashiq, Murtaza
ABSTRACT: The Arab World, a regional block of 22 countries, has been the epicenter of knowledge and innovation for many centuries. After the gap and neglect of centuries, the region is undergoing reforms that would increase scientific activities. Using the InCites tool of Clarivate Analytics, this study used bibliometric indicators of research impact and productivity to present the dynamics of the Arab World's research published between 1980 and 2020. The findings disclose that the first two decades of the 21st century witnessed a significant increase in research productivity in the region consistent with the Arab World's recent initiatives to promote scientific research. Saudi publications attracted the highest number of citations. Almost half of the region's research has collaborated internationally. The region performed better than the world in several indicators like citation impact, impact factor publications, and international collaborations; however, the region's performance lags behind the world in academic-industry collaborations and publications in Q1 journals and impact relative to the world indicators. The study recommends adopting the open access model of publishing for increased visibility and impact based on the findings. Increased attention is needed in the region to enhance research linkages between universities and industry.